Towards Environmental Sustainability: Integrating RS and GIS for Ecology Assessment - Singh, Saurabh; Jat, Mahesh Kumar; Kumar, Sudhir (European Journal of Sustainable Development, 2024)
The environment provides numerous benefits for human well-being, such as ecosystem services. These services directly and indirectly depend on the physical state of the ecosystem. However, the over-exploitation of natural resources along with socio-economic factors, i.e. economic growth, poverty, agriculture expansion, population growth and weak environmental governance and regulation for fulfilling the human needs for food, fuel, and shelter, is leading to the degradation of the ecological health of an area. Therefore, monitoring and assessment of spatial and temporal changes in the ecology of a region in terms of vital ecological services is very critical and would help the decision-makers to develop and plan appropriate adaptation and mitigation measures for the conservation of natural ecosystems at various scales to ensure environmental sustainability. The present study aimed to assess the ecological status of the Mahi Bajaj Sagar catchment area in Rajasthan (India) from the year 2000 to 2020, using remote sensing-based indices. Indicators such as greenness, dryness, and heat index have been selected as per the pressure-state-response (PSR) framework. Multi-spectral remote sensing data and image processing methods have been used to estimate these indicators, and a remote sensing-based Ecological Status Index (RSBI) has been generated by their integration using the principal component analysis (PCA) to assess the ecological status of the Mahi Bajaj Sagar catchment. Findings from the study indicate a consistent decline in the overall ecological status of the Mahi Bajaj catchment, where decreased forest areas have a pronounced effect on ecological health. Interestingly, approximately 43.6% of the area displayed resilience to changes in ecological status; however, 36.4% of the area exhibited signs of ecological degradation. Our study underscores the efficacy of a remote sensing-based approach in quantifying and detecting ecological changes, offering a promising methodology for monitoring and assessing the ecological health of large areas that can help promote environmental sustainability. Keywords: Environmental Sustainability, Ecological Status, RSBI, Remote Sensing, PSR Framework